If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(2) + 7(2) = 50 Reorder the terms for easier multiplication: 9 * 2x + 7(2) = 50 Multiply 9 * 2 18x + 7(2) = 50 Multiply 7 * 2 18x + 14 = 50 Reorder the terms: 14 + 18x = 50 Solving 14 + 18x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 18x = 50 + -14 Combine like terms: 14 + -14 = 0 0 + 18x = 50 + -14 18x = 50 + -14 Combine like terms: 50 + -14 = 36 18x = 36 Divide each side by '18'. x = 2 Simplifying x = 2
| (3+5x)(2-3x)=12-15x*2 | | 64+11x=20 | | 40=-2(23-z)+3(z-3) | | 15m+1=46 | | 2x(2)+4(2)=20 | | x^2+30x=-10 | | (10a-4)+(8a+6)+(6a-2)=360 | | (X-2)^3/4=8 | | N/=1.2 | | 5TanA+9=0 | | log(2v+4)=log(3v-2) | | 5=4/6y | | 2.4=7.44 | | Sin^-1(5/14) | | -9x+12+4(3x-3)=7(x-2)-4x | | 7+2x=3+x | | 3=5b+18 | | x+1(4)=24 | | 2x-[14x-2(x+3)-(2x+3)-(2x+3)]=16x+9 | | V=1/3×3.14r^2 | | 48=x(13+x) | | 25-8(n+2)=1 | | 13(x-9)-2=7x-5 | | -3x+16=28 | | 10x^2-16=0 | | 17y-8y=63 | | 1+y=-y-13 | | -6(x-4)+2=68 | | y=5x^2+3x-1 | | 1+y=-y-31 | | x=5y^2+3y-1 | | 2z+5=5z-8 |